Establishment of a murine model of congenital toxoplasmosis and validation of a qPCR assay to assess the parasite load in maternal and fetal tissues - Souza, Jéssica S.; Farani, Priscila S. G.; Ferreira, Beatriz I. S.; Barbosa, Helene S.; Menna-Barreto, Rubem F. S.; Moreira, Otacilio C.; Mariante, Rafael M. (Frontiers in Microbiology, 2023)
Toxoplasma gondii is the causative agent of toxoplasmosis, a disease that affects warm-blooded animals and one third of the human population worldwide. Pregnant women who have never been exposed to the parasite constitute an important risk group, as infection during pregnancy often leads to congenital toxoplasmosis, the most severe form of the disease. Current therapy for toxoplasmosis is the same as it was fifty years ago and has little or no effect when vertical transmission occurs. Therefore, it is urgent to develop new strategies to prevent mother-to-fetus transmission. The implementation of experimental animal models of congenital toxoplasmosis that reproduces the transmission rates and clinical signs in humans opens an avenue of possibilities to interfere in the progression of the disease. In addition, knowing the parasite load in maternal and fetal tissues after infection, which may be related to organ abnormalities and disease outcome, is another important step in designing a promising intervention strategy. Therefore, we implemented here a murine model of congenital toxoplasmosis with outbred Swiss Webster mice infected intravenously with tachyzoites of the ME49 strain of T. gondii that mimics the frequency of transmission of the parasite, as well as important clinical signs of human congenital toxoplasmosis, such as macrocephaly, in addition to providing a highly sensitive quantitative real-time PCR assay to assess parasite load in mouse tissues. As the disease is not restricted to humans, also affecting several domestic animals, including companion animals and livestock, they can also benefit from the model presented in this study.